The income equality dividend in 'green' infrastructure: Evidence from the transport and waste sectors in the OECD. (15th September 2021) - Valenzuela-Levi, Nicolás; Abreu, Maria
Abstract: As it is exemplified by the Sustainable Development Goals, countries are expected to advance towards both decreasing environmental harmfulness and reducing income inequality. However, although debates can be found on how to succeed in each of these two challenges, less is known about how income distribution is affecting environmental achievements. In this article, the authors propose the concept of an 'income equality dividend' regarding adoption of sustainable modes within infrastructure networks in high income countries. Evidence is provided to show that more egalitarian countries do better adopting mature environmental technologies within infrastructure networks, such as municipal recycling and railway passenger transport. Panel data from the OECD, covering between 1996 and 2013, shows that the adoption rates of these environmental technologies are higher in countries with more egalitarian income distributions. The use of instrumental variables allows to prove that the link is exogenous. In addition, adoption of mature environmental technologies seems to respond more strongly to changes in the income shared by different groups, depending on the sector. While railway passenger transport is more strongly linked to changes in shares of the bottom 40 per cent and the top 10 per cent, municipal recycling is linked to income shares by the upper half of the bottom 40 per cent, and not affected at all by the share of the rich. The income equality dividend can be explained both due to changes in consumer behaviour on the demand side, and to institutional factors reflected by income distribution, on the supply side.